ANXIETY IN ORAL ENGLISH CLASSROOMS: A CASE STUDY IN CHINA - Meihua Liu (Universitas Katolik Indonesia Atma Jaya, 2007)
This paper reports the result of a case study on anxiety in oral English classrooms in a Chinese university. By way of survey and reflective journals, the study revealed that (1) anxiety was experienced by a considerable number of students when speaking English in class, (2) the students reported to be the most anxious when singled out to speak English in class or giving presentations at the front while the least during pair work, (3) a multitude of variables such as lack of vocabulary, low English proficiency and memory disassociation contributed to student anxiety in class, and (4) most students felt helpless about being anxious when speaking English in class. Finally, some suggestions were discussed in order to help students reduce anxiety and become more confident to speak English in oral language classrooms, thus ultimately enhance their learning of oral English. Keywords: anxiety, oral English classroom, Chinese University